Tailoring composite gel polymer electrolytes with regularly arranged pores and silica particles for sodium metal batteries via breath-figure self-assembly - Kwon, Da-Sol; Jeong, Daun; Kang, Hyun Beom; Chang, Wonyoung; Bang, Joona; Shim, Jimin (Royal Society of Chemistry, 2024)
Sodium (Na) metal batteries offer a promising alternative to lithium (Li) counterparts, leveraging the abundant and cost-effective nature of Na metal. However, the development of optimized separators and polymer electrolytes remains essential for Na metal systems. Herein, we propose a novel approach to prepare composite gel polymer electrolytes by embedding regularly distributed silica particles within a porous poly(vinylidene fluoride-co-hexafluoropropylene) (PVH) matrix through static breath-figure self-assembly. This method enables the incorporation of high silica particle loadings, up to 70 wt%, ensuring thermal and mechanical stability, high ionic conductivity, and effective suppression of Na dendrite formation. Post-mortem analyses, employing in-depth X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (TOF-SIMS), offer valuable insights into how these composite gel polymer electrolytes influence the cycling performance of Na metal batteries. This study presents a straightforward and efficient strategy for fabricating composite gel polymer electrolytes to enhance the performance of Na metal batteries.